Plan de marketing para la internacionalización de la empresa " Artesanías Otavalo" - Viveros, Sara N. (2019)
The present investigation proposes the design of a marketing plan for the micro company named as Artesanías Otavalo. This plan includes 7 steps that belong to the model of John Daniels, which intent to generate strategies for the improvement of the company. In this project, three chapters are presented: the theoretical framework, the methodological framework and, lastly, the development of the results. Chapter I deals with the theoretical framework in which information and background of micro companies of the textile sector, as well as the theoretical foundations of marketing, which are composed by theoretical bases created so far and the system of variables where the vision and marketing concepts are embodied. Regarding chapter two, referring to the diagnosis, it presents the techniques and tools used for the collection of information. In chapter three, the marketing plan is developed. This chapter shows the best way and strategy to publicize the company, proposing both advertising and promotion strategies that increase the level of competitiveness and allow the company the internationalization. Finally, after this chapter it is included the conclusions and the recommendations.